The uncommon function and mechanism of the common enzyme glyceraldehyde-3-phosphate dehydrogenase in the metamorphosis of Helicoverpa armigera - Zhao, Wenli; Zhang, Bo; Geng, Zichen; Chang, Yanpeng; Wei, Jizhen; An, Shiheng (Frontiers in Bioengineering and Biotechnology, 2022)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a key enzyme in glycolysis, is commonly used as an internal reference gene in humans, mice and insects. However, the function of GAPDH in insect development, especially in metamorphosis, has not been reported. In present study, Helicoverpa armigera and Spodoptera frugiperda ovarian cell line (Sf9 cells) were used as materials to study the function and molecular mechanism of GAPDH in larvae metamorphosis. The results showed that HaGAPDH was more closely related to GAPDH of Spodoptera frugiperda and Spodoptera litura. The transcripts peaks of HaGAPDH in sixth instar larvae were 6L-3 (epidermal and midgut) and 6L-1 (fat body) days, respectively, and 20E and methoprene significantly up-regulated the transcripts of HaGAPDH of larvae in qRT-PCR. HaGAPDH-GFP-His was specifically localized in mitochondria in Sf9 cells. Knockdown of HaGAPDH by RNA interference (RNAi) in sixth instar larvae resulted in weight loss, increased mortality, and decreases in pupation rate and emergence rates. HaGAPDH directly bound to soluble trehalase (HaTreh1) physically and under 20E treatment in Yeast two-hybrid, co-immunoprecipitation, and co-localization experiments. In addition, knockdown of HaGAPDH increased Treh1 activity, which in turn decreased trehalose content but increased glucose content in larvae. Therefore, these data demonstrated that GAPDH controlled glucose content within the normal range to ensure glucose metabolism and metamorphosis by directly binding with HaTreh1.